Ekoteologi Seyyed Hossein Nasr sebagai Landasan dalam Pendidikan Agama Islam - Karunia Hazyimara (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
The increasingly complex global environmental crisis indicates that ecological problems are not merely technical in nature but are rooted in the way humans perceive nature. Ironically, environmental degradation is also prevalent in regions with predominantly Muslim populations, despite the Qur’an containing strong ecological ethical values. This condition suggests a failure in the internalization of religious values within the education system, particularly in Islamic Religious Education. This study aims to analyze Seyyed Hossein Nasr’s ecotheological thought and examine its relevance as a conceptual foundation in Islamic Religious Education, especially in fostering students’ ecological and spiritual awareness. This research employs a qualitative approach using a library research method by analyzing Nasr’s works and contemporary literature on ecotheology and Islamic education. The findings reveal that Nasr’s critique of modernity—which views nature merely as an object of exploitation—holds strong relevance for the development of Islamic Religious Education oriented toward the internalization of tawhid, amanah (trust), and adab (ethical conduct) toward nature. Nasr’s ecotheology can serve as a pedagogical foundation to shift Islamic Religious Education from a cognitive-normative approach toward the sustainable formation of students’ ecotheological character. Therefore, this study emphasizes that Islamic Religious Education has a strategic role in responding to environmental crises through strengthening the spiritual and ethical dimensions of human-nature relationships